Non-Isolated Power Factor Corrected AC/DC Converter with High Step-Down Voltage Ratio for Low-Power Applications - Lalitha T. S. Annambhotla; P. Parthiban (International Transactions on Electrical Energy Systems)
This paper proposes a high step-down ratio AC-DC converter employing a quadratic buck converter with power factor correction. Conventional active power factor correction topologies employ boost-based correction schemes for unity power factor operation. This will require a steeper step-down ratio and higher switch voltage stress apart from complexity in the control scheme with sensors. The structure of the proposed topology is developed by combining the power factor correction stage with a high step-down stage. The passive input filter is split up into two for the purpose of reducing the thermal heating apart from offering a higher power factor. A single switch operation reduces the complexity of the control scheme. In addition, the number of conducting devices during the current path is also the same as the conventional buck converter due to cascading and hence offers lower conduction losses. The need for the converter to operate at an extremely low duty cycle is reduced due to the quadratic stage structure. The proposed converter operates at a moderate duty cycle, offering higher step-down voltage apart from reducing filtering requirements. MATLAB R2020b is used for carrying out simulation studies. Xilinx FPGA-based controller using system generator is implemented for the generation of pulses of appropriate duty cycle. Simulation and experimental results for a 150 W prototype are presented. An investigation and comparative evaluation of the conventional bridgeless buck system with the quadratic buck converter are carried out. The proposed structure offers the benefit of a higher step-down voltage ratio incorporating an inherent power factor correction stage along with the AC/DC stage.